2016
DOI: 10.4088/jcp.15m09872
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Cardiovascular Diseases and Stroke Events in Methamphetamine Users

Abstract: Methamphetamine use is significantly associated with a risk of subsequent cardiovascular and cerebrovascular complications. Age appears to be an effect modifier for the risk estimation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 0 publications
6
70
0
2
Order By: Relevance
“…The authors also noted a dramatic increase in the rate of amphetamine-associated stroke over the 3-year timeframe of their study, which was greater than the rate of increase in strokes associated with any other illicit drug. Consistent with these findings, Huang and coworkers26 compared stroke events in a large cohort of methamphetamine users of all ages and found significantly increased risk of haemorrhagic stroke among methamphetamine users, but not of ischaemic stroke.…”
Section: Resultsmentioning
confidence: 74%
“…The authors also noted a dramatic increase in the rate of amphetamine-associated stroke over the 3-year timeframe of their study, which was greater than the rate of increase in strokes associated with any other illicit drug. Consistent with these findings, Huang and coworkers26 compared stroke events in a large cohort of methamphetamine users of all ages and found significantly increased risk of haemorrhagic stroke among methamphetamine users, but not of ischaemic stroke.…”
Section: Resultsmentioning
confidence: 74%
“…We found a 15% prevalence of MAMP deaths with cerebral hemorrhage also listed as a cause of death, which may be explained by the wider age range of our sample. The study by Lappin and colleagues (2017) also suggested that methamphetamine, with a longer half-life than cocaine (Karch et al, 2009), would more often subject its users to hypertension and produce increased risk of cerebrovascular events (Petitti et al, 1998; Westover et al, 2007; Huang et al, 2016). While the prevalence of cerebral hemorrhage was higher for MAMP compared to cocaine deaths in the present study, there were no statistically significant differences in multivariable analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Cocaine use is strongly associated with electrophysiological and cellular cardiac toxicity (Stankowski et al, 2015), and MAMP is known to increase heart rate and blood pressure (Huang et al, 2016; Karch, 2009; Kaye et al, 2007), likely exerting physiologic and anatomic strain on the cardiovascular system. In a national study, stimulant deaths were most common among men between the ages of 45–54 and hypertension or other cardiac causes of death were common (Calcaterra & Binswanger, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Methamphetamine, a widely abused and highly addictive substance, may cause widespread organ toxicity due to its central and peripheral sympathomimetic properties. As literature supporting the association between methamphetamine exposure and cardiovascular and cerebrovascular events mainly includes case reports, case series, postmortem studies and cross-sectional design-based research, Huang et al [13] conducted a longitudinal cohort study with observation time ranging from 10 to 14 years by analyzing a nationwide Taiwanese population-based claims data set to assess the long-term cardiovascular and cerebrovascular complications among methamphetamine users. They retrospectively selected 1,315 inpatients treated for methamphetamine use between January 1, 1997, and December 31, 2000 (nested database), and matched them with a population proxy comparison group at a ratio of 1:4 through propensity score matching.…”
Section: Physical Consequences Of Mental Illnessmentioning
confidence: 99%